Field‐Structured Polymer Composites. Issue 1 (23rd August 2013) - Martin, James E.; Bowman, Christopher N.; Horkay, Ferenc
Summary The use of multiaxial magnetic fields to create particle composites with controlled structures and properties is discussed. These field‐structured composites can have greatly enhanced isotropic or anisotropic properties, and have applications to sensing, actuation, and thermal transport. In this article the synthesis of these materials is discussed, and a variety of composite structures are shown. The magnetic permeability and thermal conductivity are given as specific examples of the utility of multiaxial field structuring.